2021
DOI: 10.3390/ijerph181910337
|View full text |Cite
|
Sign up to set email alerts
|

The Abbreviated Overall Anxiety Severity and Impairment Scale (OASIS) and the Abbreviated Overall Depression Severity and Impairment Scale (ODSIS): Psychometric Properties and Evaluation of the Czech Versions

Abstract: Short and effective tools for measuring depression, anxiety and their resulting impairments are lacking in the Czech language. The abbreviated versions of the Overall Anxiety Severity and Impairment Scale (OASIS) and the Overall Depression Severity and Impairment Scale (ODSIS) show very good psychometric properties in English and other languages, and can be used in different settings for research or clinical purposes. The aim of this study was the psychometric evaluation and validation of the Czech versions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 44 publications
8
20
0
Order By: Relevance
“…This study found that the OASIS measures anxiety equivalently between males and females on configural, metric scalar and strict levels. This finding aligns with results of the previous study [59] examining measurement invariance between males and females. Thus, the present study provides further support that differences between the two sexes can be most likely attributed to the actual differences in anxiety rather than to differences related to other factors such as biased responding [60].…”
Section: Discussionsupporting
confidence: 92%
“…This study found that the OASIS measures anxiety equivalently between males and females on configural, metric scalar and strict levels. This finding aligns with results of the previous study [59] examining measurement invariance between males and females. Thus, the present study provides further support that differences between the two sexes can be most likely attributed to the actual differences in anxiety rather than to differences related to other factors such as biased responding [60].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to depression and anxiety ( 60 ), Slovak students also showed increased levels of stress during the pandemic ( 61 ). There is less evidence in Czech Republic, but even in that country, it was possible to speak of worrying levels of stress, depression, and anxiety during the pandemic, not only among students but also in the general population ( 48 , 62 ). In fact, action is needed at the social, professional, legislative, and political levels ( 23 , 63 , 64 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both scales are being used increasingly in different countries (OASIS [ 29 , 32 , 33 , 34 , 35 ]) and (ODSIS [ 30 , 35 , 36 ]) and have shown excellent internal consistency (i.e., between 0.80 and 0.94). Different cut-off points have been found in both scales in clinical samples, the ones found for the OASIS has ranged from 5 to 10 [ 26 , 33 , 37 , 38 , 39 , 40 , 41 ] and for the ODSIS, from 5 to 11 [ 38 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different cut-off points have been found in both scales in clinical samples, the ones found for the OASIS has ranged from 5 to 10 [ 26 , 33 , 37 , 38 , 39 , 40 , 41 ] and for the ODSIS, from 5 to 11 [ 38 , 42 ]. The ROC curve analysis has been also used in a recent study in a community sample showing a cut-off point of 15 for the OASIS and 12 for the ODSIS [ 35 ]. Among the studies that have included a sample composed of clinical and non-clinical samples or students, the analysis of the ROC curve for both scales has been performed only with the subsample of clinical participants [ 30 , 32 , 36 , 43 ].…”
Section: Introductionmentioning
confidence: 99%